Analisis Agency Cost, Struktur Kepemilikan dan Mekanisme Corporate Governance - Faisal Faisal (The Indonesian Journal of Accounting Research, 2013)
This paper examines the relationship between ownership structure, corporate governance and agency costs measured in terms of asset utilization and operating expense. This paper based on the previous research by Ang et al. (1999) and Singh et al. (2003). I utilize a sample of 96 firms from Jakarta Stock Exchange for periods of 1999-2001. Univariate results show that firms with  high managerial ownership are more efficient in their asset utilization than firms with low managerial ownership, but the difference is insignificant. Firms with high institutional ownership and large size of boards are significantly more efficient than low those of  institututional ownership and small size of boards. Multivariate results fail to confirm that managerial and institutional ownership  have potential  effect to agency costs (asset utilization and operating expense). However, I  find there is a positive relationship between board size and asset utilization and negative relationship to operating expense. This evidence is consistent with the notion that large boards are  effective to monitor firm performance.